Psilocybin does not induce the vulnerability marker HSP70 in neurons susceptible to Olney’s lesions - Iorgu, Ana-Maria; Vasilescu, Andrei-Nicolae; Pfeiffer, Natascha; Spanagel, Rainer; Mallien, Anne Stephanie; Inta, Dragos; Gass, Peter (European archives of psychiatry and clinical neuroscience, 2023)
S-ketamine, a N-methyl-D-aspartate receptor (NMDAR) antagonist, and psilocybin, a 5-hydroxy-tryptamine (serotonin) 2A receptor (5-HT2AR) agonist, are reported as effective rapid-acting antidepressants. Both compounds increase glutamate signalling and evoke cortical hyperexcitation. S-ketamine induces neurotoxicity especially in the retrosplenial cortex (Olney’s lesions). Whether psilocybin produces similar neurotoxic effects has so far not been investigated. We performed an immunohistochemical whole-brain mapping for heat shock protein 70 (HSP70) in rats treated with psilocybin, S-ketamine, and MK-801. In contrast to S-ketamine- and MK-801-treated animals, we did not detect any HSP70-positive neurons in retrosplenial cortex of rats treated with psilocybin. Our results suggest that psilocybin might be safer for clinical use compared to S-ketamine regarding neuronal damage.